2018
DOI: 10.3390/nu10121860
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a High-Dose Vitamin B Multivitamin Supplement on the Relationship between Brain Metabolism and Blood Biomarkers of Oxidative Stress: A Randomized Control Trial

Abstract: A diet rich in B-group vitamins is essential for optimal body and brain function, and insufficient amounts of such vitamins have been associated with higher levels of neural inflammation and oxidative stress, as marked by increased blood plasma homocysteine. Neural biomarkers of oxidative stress quantified through proton magnetic spectroscopy (1H-MRS) are not well understood, and the relationship between such neural and blood biomarkers is seldom studied. The current study addresses this gap by investigating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 35 publications
1
53
0
Order By: Relevance
“…Along with the positive effect of ascorbic acid on BDNF expression, ascorbic acid is vital for neuronal differentiation and development, and myelin formation [54]. As vitamin B has a similar effect, such as the promotion of myelination and reduction of oxidative stress, co-administration of ascorbic acid with vitamin B as a multi-vitamin will help to protect the developing brain from Pb-induced neurotoxicity [55]. Additionally, the fact that remyelination of the nervous system is the goal of both the researcher and clinician [56], the mechanism of direct or indirect involvement of OPN in myelination will provide critical clues for development, regeneration, and therapy to demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the positive effect of ascorbic acid on BDNF expression, ascorbic acid is vital for neuronal differentiation and development, and myelin formation [54]. As vitamin B has a similar effect, such as the promotion of myelination and reduction of oxidative stress, co-administration of ascorbic acid with vitamin B as a multi-vitamin will help to protect the developing brain from Pb-induced neurotoxicity [55]. Additionally, the fact that remyelination of the nervous system is the goal of both the researcher and clinician [56], the mechanism of direct or indirect involvement of OPN in myelination will provide critical clues for development, regeneration, and therapy to demyelinating diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged periods (6 months) with high-doses (exceeding daily intake recommendations for adults) of B-group multivitamins was carried out within an RCT trial with 32 healthy adults and improved levels of total plasma homocysteine, as a marker of oxidative stress [ 289 ]. Homocysteine is associated with oxidative stress and is known to increase during B-vitamin deficiencies, especially folate and vitamin B 12 .…”
Section: Dietary Constituents As Key Factors Of a Strong Immune Symentioning
confidence: 99%
“…It can be determined by a protein marker called homocysteine. In a short-term (6 month) randomized controlled trial (RCT), it had been shown that multivitamin therapy, predominantly with vitamin B complexes, can alleviate the increased level of plasma homocysteine (Ford et al, 2018). Similar results were observed in the long term RCT of 7 years.…”
Section: B Vitaminsmentioning
confidence: 64%